Effect of waste matrix for the optimization of moisture content and calorific value of biodried material using Taguchi DOE - Mohammed, M.; Ozbay, I.; Karademir, A.; Donkor, A. (Drying Technology, 2018)
In this study, Taguchi approach was used to determine the influence of waste composition for the optimization of moisture content (MC) and calorific value (CV) of food waste via bio-drying process. The objective was to reduce MC and increase CV of the bio-dried material. The effect of three different levels of four factors including food (FW), paper (Pa), plastic (Pl) waste, and bulking agent (BA) were studied and optimized. The moisture content of the bio-dried material varied between 8.59 and 50.93%, whereas that of the calorific value was 11–25 MJ/kg. The results revealed optimum configurations for MC and CV as FW1Pa3Pl3BA3 and FW1Pa1Pl3BA1, respectively. Regression analysis revealed MC as a positive function of FW and BA with plastic positively correlated with calorific value. ANOVA analysis indicated that FW had more prominent effect on both MC and CV. The predicted and measured values were very close to each other. Additionally, the results realized in the confirmatory experiments at optimized conditions of CV was found to be higher than the test runs of Taguchi design, suggesting that Taguchi method was very successful in the optimization of bio-drying factors for MC and CV.
Keywords: Moisture content; Calorific value; Taguchi design; Optimization; Food waste